Az újonnan belépett és a jelölt országok gazdaságának fejlődése a kezdetektől 2007-ig - Burgerné Gimes, Anna (Közép-Európai Közlemények, 2009)
This article deals with the economies of ten new and three potential member countries namely, those of Bulgaria, Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovak Republic, Slovenia and Albania, Croatia and Serbia. Agriculture has a prominent role in the analyses.